1996
DOI: 10.1002/macp.1996.021971102
|View full text |Cite
|
Sign up to set email alerts
|

Polymerizations of butadiene with Ni(acac)2‐methylaluminoxane catalysts

Abstract: Polymerizations of butadiene (BD) with transition metals (MtX) and methylaluminoxane (MAO) catalysts were studied. Among the catalysts examined, nickel(I1) acetylacetonate [Ni(acach] in combination with MA0 revealed the highest catalytic activities for the polymerization of BD, giving high molecular weight polymers consisting of mainly cis-1,4-units in the microstructure. With Ni(aca~)~-MA0 catalyst, the overall activation energy for the polymerization of BD between 0°C and 60°C was estimated to be 18 kJ/mol.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
2

Year Published

1997
1997
2006
2006

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 17 publications
3
44
2
Order By: Relevance
“…The M n of the polymer increased with a decrease of reaction temperatures, but the values of M w /M n of the polymers were around 3.0 regardless of reaction temperature. The results are in a agreement with the polymerization by a homogeneous Ni(acac) 2 /MAO catalyst 17) .…”
Section: Effects Of Reaction Temperaturesupporting
confidence: 87%
See 2 more Smart Citations
“…The M n of the polymer increased with a decrease of reaction temperatures, but the values of M w /M n of the polymers were around 3.0 regardless of reaction temperature. The results are in a agreement with the polymerization by a homogeneous Ni(acac) 2 /MAO catalyst 17) .…”
Section: Effects Of Reaction Temperaturesupporting
confidence: 87%
“…Among transition metals catalyzed the polymerization of Bd, Ni-based catalysts are interesting ones from the viewpoints of not only polymerization capabilities for versatile monomers such as cyclic olefins [1][2][3][4] , ethylene or 1-olefins [5][6][7][8][9] , styrene and its derivatives [10][11][12][13][14] , conjugated dienes [15][16][17][18] , and methacrylic monomers [19][20][21] but also an advantage to require a lesser amount of methylaluminoxane (MAO) as a cocatalyst to reach a high activity for the polymerization as compared with metallocene catalysts 7,[10][11][12][13][14][15][16][17][18][19][20] . The polymerizations of many monomers such as styrene 11) , Bd 17) , isoprene 18) , methyl methacrylate 19) with Ni(acac) 2 /MAO catalyst proceeded. In a previous paper 17) , we reported that the polymerization of Bd was initiated with NiX 2 /MAO (Xϭacac or h 5 -C 5 H 5 ) catalyst to give high 1,4-cis polymer 17) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later it has been found that catalyst systems composed of a Ti, Co, Ni, V, or rare earth metal compound and an organoaluminum give cis-1,4-polybutadiene [1][2][3]. There has been recent interest in the use of soluble transition metal catalysts such as titanocene/methylalumoxane (MAO) catalysts [4], Ti(OiPr) 4 /MAO [5], Ti(CH 2 Ph) 4 / MAO [6], Ni(acac) 2 /MAO [7], and Ni(oct) 2 /AlF 3 /AlEt 3 [8] for 1,4-polymerizations of isoprene and 1,3-butadiene (BD) to obtain high molecular weight (MW) polymers with low polydispersities as efficient low-cost materials for improved synthetic rubber. The mechanism of diolefin polymerizations with various transition metal initiator systems was deeply studied and reviewed by Porri and coworkers [3].…”
Section: Introductionmentioning
confidence: 99%
“…22 Thus, it is interesting to know whether the Ni(acac)z-MAO catalyst is effective for the polymerization of isoprene (IP) and produces high cis-1,4 polymers as well as the polymerization of BO. 22 In this article, we investigate the polymerization of IP with MtX-MAO catalysts, especially Ni(acac)z-MAO catalyst.When copolymerizations of St and IP with anionic catalysts such as alkyllithiums were carried out, random copolymers were not produced, and IP units were incorporated predominantly into the copolymers. 23 · 24 Copolymerizations of St and IP with CpTiC13-MAO catalyst have been reported to produce fairly random copolymers, 25 • 26 but the Ni(acac)z-MAO catalyst was not examined.…”
mentioning
confidence: 99%